2000
DOI: 10.1177/002580240004000405
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Treatment of Opiate Users in Police Custody

Abstract: All detainees admitted to seven London police stations were observed over a six-month period (n=2,947). Four per cent were identified as opiate users, although the actual percentage is likely to be much higher. Compared to the general population of detainees there were significantly more women among known opiate users and this group also contained a higher percentage of white detainees and people born in the British Isles. People born in continental European countries were also over-represented. A little more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Complexity and mixed pathology across domains have emerged as key themes (Rekrut-Lapa & Lapa, 2014;McKinnon & Grubin, 2010;PayneJames, Green, Green, McLachlan, Munro & Moore, 2010). High levels of substance use and dependence have been identified, with a wide range of substances (both legal and illegal) being consumed, and serious problems arising in police stations as a consequence of both substance intoxication and withdrawal (Clement, Gerardin, Victorri, Guigand, Wainstein & Jolliet, 2013;Dorn, Ceelen, Buster, Stirbu, Donker & Das, 2014;Coulton, Newbury-Birch, Cassidy, Dale, Deluca, Gilvarry, Godfrey, Heather, Kaner & Oyefeso, 2012;Payne-James, Wall & Bailey, 2005;Pearson, Robertson & Gibb, 2000). Substance use also plays an important role in deaths and near miss incidents in police custody suites (Best, Havis, Payne-James & Stark, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Complexity and mixed pathology across domains have emerged as key themes (Rekrut-Lapa & Lapa, 2014;McKinnon & Grubin, 2010;PayneJames, Green, Green, McLachlan, Munro & Moore, 2010). High levels of substance use and dependence have been identified, with a wide range of substances (both legal and illegal) being consumed, and serious problems arising in police stations as a consequence of both substance intoxication and withdrawal (Clement, Gerardin, Victorri, Guigand, Wainstein & Jolliet, 2013;Dorn, Ceelen, Buster, Stirbu, Donker & Das, 2014;Coulton, Newbury-Birch, Cassidy, Dale, Deluca, Gilvarry, Godfrey, Heather, Kaner & Oyefeso, 2012;Payne-James, Wall & Bailey, 2005;Pearson, Robertson & Gibb, 2000). Substance use also plays an important role in deaths and near miss incidents in police custody suites (Best, Havis, Payne-James & Stark, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pearson et al (2000) found the mean age of 115 detainees to be 29 years, with the proportion of women at 28%. In our sample, the mean age was 28 years and 27% were women.…”
Section: Discussionmentioning
confidence: 99%
“…[11] pointed out that 26% of pharmacists in Scotland dispensed DHC and Pearson et al . [12] observed that DHC is the most common medication given to opiate misusers to manage opiate withdrawal symptoms in police custody in seven London areas.…”
Section: Introductionmentioning
confidence: 99%